Spontaneous Flexor Tendon Rupture due to Primary Distal Radioulnar Joint Osteoarthritis - Akira Hashimoto; Motoki Sonohata; Hideyuki Senba; Masaaki Mawatari (Case Reports in Orthopedics)
Spontaneous flexor tendon rupture is rare, occurring most commonly in the little finger or flexor pollicis longus. To the best of our knowledge, there have been no reports of spontaneous flexor tendon rupture due to primary distal radioulnar joint (DRUJ) osteoarthritis (OA). We present a case of spontaneous flexor tendon rupture in the index finger due to primary DRUJ OA in a 71-year-old female farmer. Surgical exploration confirmed that, at the wrist joint level, the flexor digitorum profundus of the index finger had undergone degeneration and complete rupture. The flexor digitorum superficialis of the index finger was elongated and thinned. A bony spur toward the volar side was covered with synovial fluid from a pinhole-sized perforation of the capsule. The combination of direct friction from the DRUJ spur and the matrix metalloproteinases in the synovial fluid from the perforation of the DRUJ capsule may have caused the spontaneous flexor tendon rupture. Palmar-side symptoms associated with DRUJ OA should be carefully examined because of the risk of spontaneous flexor tendon rupture.